Jawabanmu

2014-06-18T19:27:28+07:00
OA = √{(a-0)²+(0-0)²} = √a² = a
OB = √{(-3-0)² + (√7-0)²} = √(9 + 7) = 4
BA = √{(a+3)²+(0-√7)²} = √{(a+3)²+7}
Misal < AOB = Ф
α+β+Ф = 180' ⇔ Ф = 180' - (α + β)
                         1/2 Ф = 1/2{180' - (α+β)}
                                   = {90' - 1/2(α+β)}
                       Sin1/2 Ф = Sin{90' - 1/2(α + β)}
                       Sin 1/2 Ф = Cos1/2(α+β)
Cos Ф = AO² + OB² - AB²
                2(OA)(OB)
           = a² + 16 - (a+3)²-7
                 2(a)(4)
           = a² + 9 - a² - 6a - 9
                     8a
           = -6a/8a
           = -3/4
Cos2(1/2 Ф) = 1 - 2Sin²1/2 Ф
     - 3/4        = 1 - 2Sin² 1/2 Ф
2Sin²1/2Ф = 1 + 3/4 = 7/4
  Sin²1/2 Ф = 7/8
  Sin 1/2 Ф = √(7/8)
                 = √7  . √2
                   2√2   √2
                 = √14
                     4
Jadi. Cos(1/2)(α + β) = Sin 1/2 Ф = (1/4)√14
1 5 1